2013
DOI: 10.1007/s11095-013-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of a Silk Sericin-Releasing Bioactive Wound Dressing for the Treatment of Split-Thickness Skin Graft Donor Sites

Abstract: We introduce this novel silk sericin-releasing wound dressing as an alternative treatment for split-thickness skin graft donor sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 30 publications
9
52
1
Order By: Relevance
“…Sericin has been previously reported to promote attachment and proliferation of various mammalian cells by the activation of collagen production. [20][21][22][23][24][25] Furthermore, we previously demonstrated that sericin influenced on collagen production of cells in a concentration-dependent manner. 26 The higher concentration of sericin activated cells to produce more collagen.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Sericin has been previously reported to promote attachment and proliferation of various mammalian cells by the activation of collagen production. [20][21][22][23][24][25] Furthermore, we previously demonstrated that sericin influenced on collagen production of cells in a concentration-dependent manner. 26 The higher concentration of sericin activated cells to produce more collagen.…”
Section: Resultsmentioning
confidence: 95%
“…20 We have intensively worked with various kinds of sericin-containing scaffolds aimed to be used as wound dressing materials. [21][22][23][24][25] The accelerated healing of wounds as a result of sericin released from the scaffolds was reported. Surprisingly, we preliminary found that sericin blended with CMC, without the use of any crosslinking agent, could be fabricated into a stable hydrogel even they are both water soluble polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Sericin is more hydrophilic than fibroin and can more effectively induce collagen synthesis in dermal tissue. It is a good candidate for use in tissue engineering scaffolding as a dressing material or skin substitute [49]. Sericin film increases the proliferation of human skin keratinocytes and fibroblasts, and it accelerates wound healing [49].…”
Section: Sericinmentioning
confidence: 99%
“…It is a good candidate for use in tissue engineering scaffolding as a dressing material or skin substitute [49]. Sericin film increases the proliferation of human skin keratinocytes and fibroblasts, and it accelerates wound healing [49]. Sericin also has antimicrobial, antioxidant, and photo-protective ability from ultraviolet radiation, so it has been effectively used as a dressing material for skin protection [50,51].…”
Section: Sericinmentioning
confidence: 99%
“…Sericin is also found to promote the activities of keratinocytes and primary cultured human fibroblasts as well as to enhance epithelialization and collagen formation (10)(11)(12)(13)(14). We have previously reported the accelerated wound healing rate in both animal and clinical trials by the application of various kinds of wound dressing releasing sericin, e.g., sericin/PVA scaffold and sericin-incorporated silk fibroin/gelatin scaffold (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%